Bilateral Symmetry before and Six Months after Aberration-Free™ Correction with the SCHWIND AMARIS TotalTech Laser: Clinical Outcomes - Arbelaez, Maria Clara (2010)
PURPOSE: To compare the preoperative and postoperative bilateral symmetry between OD and OS eyes that have undergone femto-LASIK using the Ziemer LDV femtosecond laser system, the SCHWIND AMARIS Excimer Laser and the Aberrationfree™ profiles implemented in the SCHWIND Custom Ablation Manager software. METHODS: A total of 25 LASIK patients were bilaterally evaluated at the six-month follow-up visit. In all cases standard examinations, pre- and postoperative analysis with corneal wavefront topography (OPTIKON Scout) were performed. Aberration-free™ aspheric treatments were devised using the Custom Ablation Manager software and ablations were performed by means of the SCHWIND AMARIS flying-spot excimer laser system (both SCHWIND eyetech- solutions). In all cases LASIK flaps were created using an LDV femtosecond laser (Ziemer Group). The OD/OS bilateral symmetry was evaluated in terms of corneal wavefront aberration. RESULTS: Preoperatively, 11 Zernike terms showed significant bilateral (OS-vs.-OD) symmetry, and only 6 Zernike terms were significantly different. Overall, 23 out of the 25 patients showed significant bilateral symmetry, and only 2 out of 25 patients showed significant differences. None of the aberration metrics changed from pre- to postoperative values by a clinically relevant amount. At the 6-month postoperative visit, 12 Zernike terms showed significant symmetry, and 8 terms were significantly different. Overall, 22 out of 25 patients showed significant bilateral symmetry (OS vs. OD), and only 3 out of 25 patients showed significant differences. Also, this postoperative examination revealed that 6 Zernike terms lost significant OS-vs.-OD symmetry, but 4 Zernike terms gained significant symmetry. Finally, 4 patients lost significant bilaterality, and 2 patients gained significant bilaterality: bilateral symmetry between eyes was better maintained in those patients with a clear preoperative bilateral symmetry. CONCLUSIONS: Aberration-Free Treatments with the SCHWIND AMARIS did not induce clinically significant aberrations, maintained the global OD-vs.-OS bilateral symmetry, as well as the bilateral symmetry between corresponding Zernike terms (which influences binocular summation).